Iodine and Selenium Biofortification with Additional Application of Salicylic Acid Affects Yield, Selected Molecular Parameters and Chemical Composition of Lettuce Plants (Lactuca sativa L. var. capitata) - Smoleń, Sylwester; Kowalska, Iwona; Czernicka, Małgorzata; Halka, Mariya; Kęska, Kinga; Sady, Włodzimierz (Frontiers in Plant Science, 2016)
Iodine (I) and selenium (Se) are included in the group of beneficial elements. They both play important roles in humans and other animals, particularly in the regulation of thyroid functioning. A substantial percentage of people around the world suffer from health disorders related to the deficiency of these elements in the diet. Salicylic acid (SA) is a compound similar to phytohormones and is known to improve the efficiency of I biofortification of plants. The influence of SA on Se enrichment of plants has not, however, been recognised together with its effect on simultaneous application of I and Se to plants. Two-year studies (2014–2015) were conducted in a greenhouse with hydroponic cultivation of lettuce in an NFT (nutrient film technique) system. They included the application of I (as KIO3), Se (as Na2SeO3) and SA into the nutrient solution. KIO3 was used at a dose of 5 mg I•dm-3 (i.e., 39.4 µM I), while Na2SeO3 was 0.5 mg Se•dm-3 (i.e., 6.3 µM Se). SA was introduced at three doses: 0.1, 1.0 and 10.0 mg∙dm-3 nutrient solutions, equivalent to 0.724 µM, 7.24 µM and 72.4 µM SA, respectively. The tested combinations were as follows: 1.) control, 2.) I + Se, 3.) I + Se + 0.1 mg SA∙dm-3, 4.) I + Se + 1.0 mg SA∙dm-3 and 5.) I + Se + 10.0 mg SA∙dm-3. The applied treatments had no significant impact on lettuce biomass (leaves and roots). Depending on the dose, a diverse influence of SA was noted with respect to the efficiency of I and Se biofortification; chemical composition of leaves; and mineral nutrition of lettuce plants, including the content of macro- and microelements and selenocysteine methyltransferase (SMT) gene expression. SA application at all tested doses comparably increased the level of selenomethionine (SeMet) and decreased the content of SA in leaves.